Prevalence of zoonotic tuberculosis and associated risk factors in Central Indian populations - Prachi R. Bapat; Renuka S. Dodkey; Seema D. Shekhawat; Aliabbas A. Husain; Amit R. Nayak; Anuja P. Kawle; Hatim F. Daginawala; Lokendra K. Singh; Rajpal S. Kashyap (Springer, 2019)
In the present study, we aimed to estimate the occurrence of bovine tuberculosis (TB) and examine the determinants of distribution of the disease in three high-risk populations of Central India. A prospective cohort study was conducted in Central India between March 2014 and June 2015. Based on the requisite inclusion criteria, we recruited a total of 301 participants whose blood samples were subjected to polymerase chain reaction-based detection and differentiation of Mycobacterium bovis and Mycobacterium tuberculosis. M. bovis was detected in 11.4%, 8.9%, and 12.6% of the recruited participants belonging to three distinct population groups (Groups A, B, and C, respectively). The highest proportion of cases infected with M. bovis was observed in Group C, who lived in the high TB endemic region. Previous contact with active TB cases (odds ratio = 3.7; 95% confidence interval, 0.9612-14.4533) and raw milk consumption (odds ratio = 5.3472; 95% confidence interval, 1.9590-14.5956) were found to be important determinants of bovine TB in this population. The high incidence rates of bovine TB in the Central Indian populations indicate the substantial consequences of this disease for some population groups and settings. However, more research is necessary to identify the main transmission drivers in these areas.